2021
DOI: 10.1159/000515011
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Hemorrhage in a Pediatric Patient with Chronic Myeloid Leukemia in Chronic Phase: A Case Report

Abstract: Chronic myeloid leukemia (CML) is an uncommon entity in pediatric patients. CML in chronic phase (CML-CP) has a relatively favorable outcome. Leukostasis occurs in 9.7% of patients with CML. One of the most serious leukostasis-related complications is intracranial hemorrhage (ICH). However, this is very rare in patients with CML-CP, and few early mortalities have been reported in CML patients with leukostasis. We report the case of a 14-year-old female patient with CML-CP who developed ICH 8 days after admissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…20 The reported cases of SNHL as an initial manifestation in juvenile CML have also revealed high WBC concentrations of 167-733 × 10 9 /L. [17][18][19] In our case, the patient had an extremely high WBC count of 780.72 × 10 9 /L and splenomegaly Schuffner 5. These data suggest that, among the multifactorial pathogenesis of CML, 5,6,8,10,17,22 the most notable in our case was hyperleukocytosis.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…20 The reported cases of SNHL as an initial manifestation in juvenile CML have also revealed high WBC concentrations of 167-733 × 10 9 /L. [17][18][19] In our case, the patient had an extremely high WBC count of 780.72 × 10 9 /L and splenomegaly Schuffner 5. These data suggest that, among the multifactorial pathogenesis of CML, 5,6,8,10,17,22 the most notable in our case was hyperleukocytosis.…”
Section: Discussionmentioning
confidence: 57%
“…25 Patients with a WBC count higher than 300 × 10 9 /L and a spleen size larger than 10 cm are more likely to develop leukostasis complications. 7,19,20 A previous 368 study on leukostasis in children and adolescents with CML reported a significantly higher median WBC concentration in leukostasis cases than in non-leukostasis cases: 458.5 × 10 9 /L versus 151.8 × 10 9 /L, respectively. 20 The reported cases of SNHL as an initial manifestation in juvenile CML have also revealed high WBC concentrations of 167-733 × 10 9 /L.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…e authors attempted auditory evoked potentials (which the patient did not cooperate to perform) and performed an MRI brain that revealed bleeds in the right lower frontal area and the anterior thalamus. Similarly, Takahashi et al [17] diagnosed a CML-CP patient from blood work who presented with fever and fatigue. e patient received hydration therapy, allopurinol, and low molecular weight heparin after her admission, while imatinib was commenced when the diagnosis was confirmed.…”
Section: Location Of Bleed Management Outcomementioning
confidence: 95%